Smooth muscle of the male pelvic floor: An anatomic study. Issue 6 (2nd December 2019) - Nyangoh Timoh, Krystel; Deffon, J.; Moszkowicz, D.; Lebacle, C.; Creze, M.; Martinovic, J.; Zaitouna, M.; Diallo, D.; Lavoue, V.; Fautrel, A.; Benoit, G.; Bessede, T.
Abstract : Knowledge of the anatomy of the male pelvic floor is important to avoid damaging the pelvic floor muscles during surgery. We set out to explore the structure and innervation of the smooth muscle (SM) of the whole pelvic floor using male fetuses. We removed en‐bloc the entire pelvis of three male fetuses. The specimens were serially sectioned before being stained with Masson's trichrome and hematoxylin and eosin, and immunostained for SMs, and somatic, adrenergic, sensory and nitrergic nerve fibers. Slides were digitized for three‐dimensional reconstruction. We individualized a middle compartment that contains SM cells. This compartment is in close relation with the levator ani muscle (LAM), rectum, and urethra. We describe a posterior part of the middle compartment posterior to the rectal wall and an anterior part anterior to the rectal wall. The anterior part is split into (1) a centro‐levator area of SM cells localized between the right and left LAM, (2) an endo‐levator area that upholsters the internal aspect of the LAM, and (3) an infra‐levator area below the LAM. All these areas are innervated by autonomic nerves coming from the inferior hypogastric plexus. The core and the infra‐levator area receive the cavernous nerve and nerves supplying the urethra. We thus demonstrate that these muscular structures are smooth and under autonomic influence. These findings are relevant for the pelvic surgeon, and especially the urologist, during radical prostatectomy, abdominoperineal resection and intersphincteric resection. Clin. Anat., 2019. © 2019 Wiley Periodicals, Inc.